STRATEGI PENGELOLAAN SEKOLAH TINGGI BERASRAMA DI KABUPATEN SEMARANG - Noveliza Rudyolindy Theodora Tepy (Kelola: Jurnal Manajemen Pendidikan, 2016)
The purpose of this study was to: (1) Determine and analyze the boarding management strategies that have been used by STT Sangkakala; (2) to analyze the root problems in the management of a boarding high school in STT Sangkakala; (3) Design and produce strategies that can be implemented by STT Sangkakala in the management of a boarding high school. Design of this research is the development, but in this study is limited to the fifth stage, namely the revision of product design, where the product that produced a strategic plan for the management of the boarding college at STT Sangkakala Kopeng. Data analysis technique used fishbone anlysis. Data collection techniques used observation, interview, document studies, and FGD. Meanwhile, data validation was done by using tianggulasi source. The results of this analysis, a strategy that is based on the analysis fishbone, includes four factors: (1) curriculum management strategies and coaching; (2) management strategies of learners; (3)management strategies educators; and (4) strategies in the policy leader. Furthermore, the foundations, the chairman (rector), lecturers and other staff are expected to optimize the implementation of the strategic plan that has been prepared.